Can Plantation Museums Do Full Justice to the Story of the Enslaved? A Discussion of Problems, Possibilities, and the Place of Memory. Issue 2 (3rd July 2018) - Modlin, E. Arnold; Hanna, Stephen P.; Carter, Perry L.; Potter, Amy E.; Bright, Candace Forbes; Alderman, Derek H.
Abstract : This article, structured as a prompt-and-response work, is authored by members of a research team investigating how slavery is absent and present at tourism plantation museums in the U.S. South. The prompt for the discussion grew out of E. Arnold Modlin's concern that, even at museums where narratives and landscapes center on enslaved people, the presence of the master and enslaver within the same space ensures that once-enslaved people are always commemorated as less than fully human subjects. In response to Modlin's prompt, Perry L. Carter, Amy E. Potter, Candace Forbes Bright, and Stephen P. Hanna deploy their field experiences as well as various literature to envision ways Southern plantation museums can and must more fully and justly commemorate enslaved persons. Derek H. Alderman, as discussant, situates this exchange within the rapidly developing literature on black geographies and emphasizes the entire research team's call for geographers to engage, or even intervene, with ongoing memory work.